Dynamic Load Balancing with Multipath Routing in Software Defined Networking - Neupane, Bijay; Pudashine, Kumar (Journal of Science and Technology, 2026)
Traditional Ethernet networks were limited to routingschemes. A single best path was used by the Spanning TreeProtocol (STP). This was a major cause for the limitation in thethroughput and the increased network latency. Multipath routingscheme is one of the solutions where multiple paths availablein the network are used for traffic forwarding. If the load isbeing forwarded to the multiple paths, load balancing finds itsapplication to balance the load among different paths. In thispaper, a multipath routing scheme is proposed along with theload balancing among the available multiple paths in SoftwareDefined Networking (SDN) environment. SDN is an emergingnetworking paradigm where control plane is separated from thedata plane. Mininet is used as the network simulation tool alongwith the Ryu controller to support network programmabilityfeature on the control plane.